Potencial fisiológico e teor de macro e micronutrientes em sementes de feijão utilizando material crioulo e melhorado por seleção participativa - Alves, Carla Xavier (2013)
The bean is consumed by a large part of the population and is an important source of nutrients, which may have their levels increased with the use of genotypes that have naturally high levels of these nutrients. In Brazil, the beans is grown mainly by small farmers, who often use seeds from previous years, selected by the farmers themselves for years, characterizing them as native seeds. These seeds are great source of genetic variability, with high potential for direct use by farmers and use in breeding programs. Knowledge of characteristics that influence the quality of seeds is crucial for the selection of the best genotypes to be used. A characteristics mentioned is the concentration of nutrients in the seeds. The study aimed to evaluate the physiological quality and nutrient content in seeds of landraces and improved cultivars for participatory selection, and the influence of the content of these nutrients in seed vigor. The seeds used were produced in São Luiz Gonzaga and Sobradinho, RS, from cultivar evaluation trials of 2011/2012 season. Were evaluated seeds: germination, accelerated aging, cold, electrical conductivity and root length and shoot length in seedlings. We also evaluated the levels of phosphorus, calcium, potassium, iron, magnesium, zinc and manganese in the seeds. It was concluded that the seeds of landraces and improved cultivars by selection participatory exhibit high physiological potential. Genotypes AM-10, AS-7, Black Iberian TB 02-21 and ZL-1 stood out at higher seed vigor. There was an interaction between genotype and environment for nutrient content in the seeds. The nutrient content influences the quality of seeds, especially phosphorus, calcium, iron and manganese.